Development of mucoadhesive hydrogels based on polyacrylic acid grafted cellulose nanocrystals for local cisplatin delivery. (1st March 2021) - Vakili, Mohammad Reza; Mohammed-Saeid, Waleed; Aljasser, Abdullah; Hopwood-Raja, Julian; Ahvazi, Behzad; Hrynets, Yuliya; Betti, Mirko; Lavasanifar, Afsaneh
Highlights: Developed a mucoadhesive material based on cellulose nano crystals (CNC). Showed superior mucoadhesion of this structure compared to poly(acrylic acid). Optimized the weight ratio of poly(acrylic acid) (PAA) to CNC. Demonstrated non-toxicity of CNC-g-PAA (on its own) against colorectal cancer cells. Illustrated a great potential for CNC-g-PAA hydrogels in mucosal drug delivery. Abstract: To fabricate a mucoadhesive hydrogel with superior properties for local delivery of cisplatin (CDDP) to colorectal cancer, a hardcore bottle-brush polymer (HCBBP) was developed through grafting of poly(acrylic acid) (PAA) on cellulose nanocrystals (CNC) at 6, 9 and 12 CNC:PAA w/w ratios. The developed materials were characterized by acid-base titrations, FT-IR, electron microscopy, muco-rheological behaviour in the presence of mucin, in vitro drug release and anticancer activity against human HCT-116 colorectal cancer cells. The results showed CNC-g-PAA9 to have superior rheological behavior in the presence of mucin compared to CNC and other gels under study indicating beneficial mucoadhesive characteristics. CNC-g-PAA9:CDDP complex showed slow CDDP release causing a significant increase in IC 50 of the drug (> 3-fold) against HCT116 cells. The developed CNC-PAA9 hydrogel showed no intrinsic cytotoxicity on its own. The results point to a great promise for CNC-g-PAA9 as mucoadhesive hydrogels for local platinum delivery in colorectal cancer.